PENAPISAN AKTIVITAS ANTIPROTOZOA DALAM BIJI SAGA (Adenanthera pavonina LINN) - Lenny Sutedja (Research Center for Chemistry - LIPI, 1995)
The protozoa Tetrahymena pyriformis GL is an eucaryote. Its metabolism is similar to that of mammalia, so that it is widely used as a biological tool in protein quality as well as toxicity assays. In the framework of searching toxic or antinutritive properties in saga seed (Adenanthera pavonina LINN), extracts of saga bean were tested for their antiprotozoa activity. The saga bean extracts were obtained after successive extraction with nhexane and ethanol. Observation of total and motile cell population indicated that 0,1% saga oil in the medium did not show significant effect on the growth of T.pyriformis GL during 96 hours incubation at 30°C. While ethanol extract of saga showed significant inhibition on the growth of T.pyriformis GL. Smaller cell population was already observed at 7 hours incubation at 30°C. At 24 hours incubation, 0,1% and 1% ethanol extract of saga in the medium showed 55,1% and 87,6% inhibition respectively. Ethanol extract showed the largest anttprotozoal activity compared to the other extract. Qualitative analysis indicated the presence of saponin and alkaloid in the ethanol extract of saga bean. Chromatographic analysis with high performance liquid chromatography showed the presence of at least eight components in the ethanol extract of saga.